Subcutaneous administration of the malaria R21/Matrix M vaccine and immune complex formation with anti-circumsporozoite protein mAb 2A10 elicit protective efficacy in mice - Mukhopadhyay, Ekta; Camacho, César López; Hill, Adrian V. S.; Salman, Ahmed M. (Frontiers in Immunology, 2025)
IntroductionR21, the most efficacious malaria vaccine to date, has been recommended by the World Health Organization (WHO) for the prevention of malaria in children. The current vaccination schedule requires three intramuscular doses per year. Optimizing vaccine administration strategies, including exploring alternative routes of immunization and novel vaccine formulations, has the potential to reduce the number of required doses to achieve high efficacy. Immune complexes (ICs), formed by combining antigens with their cognate antibodies, have been successfully employed in licensed poultry vaccines for viral diseases and are showing promise in preclinical studies for human viral vaccines. Co-delivery of antigen with immune complexes has been reported to enhance antibody titers in preclinical models.MethodsHere, we present the first report of the immunogenicity and short- term high protective efficacy of R21/Matrix-M administered via the subcutaneous (SC) route, as well as in a modified formulation as an immune complex (IC) (R21: anti-NANP mAb 2A10) with only two immunizations. We also evaluated co-administration of R21 with pre-formed ICs.ResultsR21/MM administered via the SC route is immunogenic and more efficacious (100% in BALB/c mice) than the IM route. R21:2A10 IC/MM is immunogenic and induces sterile protection in BALB/c mice. Co-administration of R21/MM with R21:2A10 IC is immunogenic but less protective than IC/MM alone in BALB/c mice.ConclusionWhile IC-based vaccination strategies have primarily been explored for viral diseases, this study represents the first application of this approach to a parasitic disease. Our findings provide new insights into the potential of alternative vaccine delivery strategies and immune complex platforms for improving malaria vaccination outcomes.